Pengaruh Mobilisasi Dini terhadap Penyembuhan Luka dan Peningkatan Aktivitas Pasien Postoperasi Laparatomi - Yuliana Yuliana; Andrew Johan; Nana Rochana (Jurnal Akademika Baiturrahim Jambi, 2021)
Laparatomy is surgery of the abdomen to open the lining of the abdomen. The treatment reduces complications due to surgery, accelerates healing and restores the patient's function to the maximum extent possible before surgery. Returns physical function immediately after surgery with early mobilization. The purpose of this study was to look at the effect of early mobilization on wound healing and increased patient activity postoperatively in laparotomy. This type of research is quantitative with quasy eksperiment with control gruop designs. The number of samples was 88 Laparatomi patients, taken using purposive sampling technique. Tool of data using observation sheets. Data were analyzed using chi-square test and Wilcoxon test. The results of the study stated that there were significant differences between the control group and the intervention group on wound healing (p= 0.047) and on increased activity (p= 0.005). The results of the study it can be concluded that there is an influence of early mobilization on wound healing and increased patient activity. The results of this study recommend early mobilization using progressive mobility procedures in accordance with client activity intolerance